Uji Validitas Modul Hukum Dasar Kimia dan Stoikiometri Berbasis Inkuiri Terbimbing - Silvia Enmi Perifta; Iryani Iryani (Edukimia, 2019)
This study aims to produce a product in the form of a module  on basic chemical laws and stoichiometry and to find out how the categories of module validity levels produced. This is Research and Development study that aims to produce a particular product. This research uses the Plomp model which consist of three stages, preliminary research, prototyping stage and asasment phase.The Instrument to be test validity in the form a validation sheet . This product is validated by 5 validators consisting of 3 lecturers of chemistry majors at FMIPA UNP and 2 teachers from SMAN 10 Padang. The result of the validation obtained the moment kappa value (k) of 0,81 so that from the value it can be said that the module produced is very valid.